The Contextual Semantic Realization of the Lexical Units Hesitate, Waver, Vacillate, Falter vs. Hesitation, Hesitancy - Gnatiuk, Alla (East European Journal of Psycholinguistics, 2017)
This article is dedicated to the research of synonymous groups for the designation of doubt “Hesitate, Waver, Vacillate, Falter” and “Hesitation, Hesitancy” in contemporary English-language fictional discourse. Doubt is defined as an epistemic state in the cognitive world of individuals which provides motivation to undertake a further quest for information. The purpose of this work is to investigate how the set of semes identified in each component of the synonymous group is presented in the context of modern English fictional discourse. This research is directed towards verifying whether the use of all the components of the given synonymous groups is of equal importance in modern language discourse, as well as checking whether all the semes of “Hesitate, Waver, Vacillate, Falter” and “Hesitation, Hesitancy” are used correctly, based on the results of the componential analysis. The results of the research make it possible to form conclusions regarding the homogeneity or heterogeneity of contextual sematic representations in discourse, dependent upon the number of constituents which make up the synonymous group.References Arthur, T. S. (2008). The Good Time Coming. Webster’s French Thesaurus Edition. SanDiego: Icon Classics. Bisson, T. (2009). Fire on the Mountain. Oakland: PM Press.Clark, M. S. (2011). Don’t Take Any Wooden Nickels. Eugene: Harvest House Publishers.Crystal, D. (1997). The Cambridge Encyclopedia of Language. Cambridge: CambridgeUniversity Press.Dijk, T. A. (1992). Text and Context: Explorations in the Semantics and Pragmatics ofDiscourse. Longman.Evans, V. (2006). Cognitive Linguistics. Introduction. Edinburgh: Edinburgh UniversityPress.Ortony, A. (1988). The Cognitive Structure of Emotions. Cambridge: Cambridge UniversityPress.Plutchik, R., Kellerman H. (1980). A General Psychoevolutionary Theory of Emotion. In:Emotion: Theory, Research and Experience. Vol. 1: Theories of Emotion, (pp. 3−31). NewYork: Academic Press.Thagard, P., Brun G., Doğuoğlu U., Kuenzle D. (2008). How Cognition Meets Emotion:Beliefs, Desires and Feelings as Neural Activity. In: Epistemology and Emotions, (pp.167−184). Hampshire: Ashgate Publishing Limited.SourcesEly, A. (1862). Journal of Alfred Ely, A Prisoner of War in Richmond. New York:D. Appleton and Company.Madrid-Null, M. H. (2006). Navajo Heat. Victoria: Trafford Publishing.Matza, D. (1964). Delinquency and Drift. New Jersey: Transaction Publishers.Merriam-Webster, A. (1947). Webster’s Dictionary of Synonyms. First Edition. ADictionary of Discriminated Synonyms with Antonyms and Analogous and ContrastedWords. Springfield, Massachusetts: Merriam Co. Publishers.